2020
DOI: 10.1016/j.dib.2019.104772
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation data for the dynamic properties of rainbow metamaterials

Abstract: Simulation data are presented for identifying and analysing the dynamic properties of the rainbow metamaterials as presented in the articles “Rainbow metamaterials for broadband multi-frequency vibration attenuation: numerical analysis and experimental validation” (Meng et al., 2019 [1]) and “Optimal design of rainbow elastic metamaterials” (Meng et al., 2019 [2]). In this data article, the frequency response functions and mode shapes of the rainbow metamaterials are numerically calculated by Finite Element mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…They act independently that it is possible to create two separate band gap regions, consequently broadening the total attenuation band. This analytical model has been previously proposed and validated by experimental results 10,11,26 and it is briefly presented here. Displacements of the Π-shaped unit cell or segment are given as 10 where the subscripts l and l stands for the left and right ends of the n -th segment at x n and xnr=xn+pnLd, respectively, where boldΛn,l=diag{eik(xxn),ek(xxn),eik(xxn),ek(xxn)}, boldΛn,r=diag{eik(xxnr),ek(xxnr),eik(xxnr),ek(...…”
Section: Metamaterials Beam With Non-symmetric Resonatorsmentioning
confidence: 99%
“…They act independently that it is possible to create two separate band gap regions, consequently broadening the total attenuation band. This analytical model has been previously proposed and validated by experimental results 10,11,26 and it is briefly presented here. Displacements of the Π-shaped unit cell or segment are given as 10 where the subscripts l and l stands for the left and right ends of the n -th segment at x n and xnr=xn+pnLd, respectively, where boldΛn,l=diag{eik(xxn),ek(xxn),eik(xxn),ek(xxn)}, boldΛn,r=diag{eik(xxnr),ek(xxnr),eik(xxnr),ek(...…”
Section: Metamaterials Beam With Non-symmetric Resonatorsmentioning
confidence: 99%
“…Chen et al [5] and Peng and Pai [6] developed metamaterial beams, plates and sandwich structures with membrane or mass spring oscillators. Meng et al [7][8][9][10] studied metamaterial beams with spatially varying cantilever-mass oscillators. Barnhart et al [11], Peng et al.…”
Section: Introductionmentioning
confidence: 99%
“…Beli et al [54] proved that the spatial correlated variability could lead to widened bandgaps for cantilever-in-mass metamaterials. Meng et al [55][56][57][58][59] investigated rainbow metamaterial beams with spatially varying oscillators and rainbow phononic crystal lattices with spatial varying mass blocks and found that the rainbow structures could generate broader bandgaps compared with periodic ones.…”
Section: Introductionmentioning
confidence: 99%